The ischemia trial: Implication for cardiac imaging in 2020 and beyond - Leipsic, Jonathon A.; Achenbach, Stephan (Radiology: Cardiothoracic Imaging, 2020)
Establishing a diagnosis of coronary artery disease (CAD) is more difficult than it would seem. Diagnosis of CAD can be approached in two ways: Detection of ischemia (often with stress myocardial perfusion at SPECT, PET, and cardiac MRI) and visualization of the coronary artery anatomy to demonstrate stenosis (noninvasively with cardiac CT). In addition to providing further supportive evidence for the use of coronary CT angiography as the first-line test for the evaluation of CAD, the ISCHEMIA trial also resulted in some interesting findings with regard to imaging; these findings resulted in the open-ended question of “What does this mean for imagers?”.
CRIS-Team Scopus Importer:2023-03-08